A sustentabilidade de agroecossistemas de produção de peixes com enfoque agroecológico na agricultura familiar - Nunes, José Simões (2016)
The study was conducted in three agroecosystems, located in three municipalities of the Cantuquiriguaçu region in the state of Paraná, Brazil. The aim of the study was to evaluate the sustainability of family-based agroecosystems with fish production, from an agroecological perspective. The Framework for Assessing the Sustainability of Natural Resource Management Systems (MESMIS) and systematic Association of Family Farming and Agroecology (ASP-TA ) methodologies were carried out in an interdisciplinary and participatory manner, addressing the attributes of sustainability and ecological, economic, social, political, cultural, ethical and fish production management dimensions. Production models were discussed towards sustainability of the three farmer’s families. Different concepts of fish production and its main features in order to achieve a more sustainable production model for family farming were presented. There were also presented and discussed highlights points found when building the radar charts. It was possible to evaluate the agroecosystems in an integrated way, with their levels of sustainability, based on the concept of sustainability identified with the families and also based on theoretical references that supported the study. Through the analysis of agroecosystems, it were identified the internal and external relations of the subsystems, allowing to visualize fish farming potential in the studied agroecosystems. Indicators were defined for the ecological (18), economic (16), social (18), politic (7), cultural (11), ethics (8) and management of fish farming (12) dimensions. Management fish farming indicators reached the lowest level (64, 67 and 72%) in the agroecosystem assessment. These results were mainly attributed to the lack of specialized rural extension and research for agroecological fish farming. Innumerous difficulties and barriers in the construction of a fish farming agroecological based production model were detected. Though, the basis for agroecological fish production are in the agroecosystem redesign, in approaching natural system reproduction, prioritizing integration and relations between the subsystems and in using the polyculture of species. It is observed that the families worked with fish farming, but not yet as a potential activity to increase agroecossystem fertility and reach sustainability.